O que não é espelho - uma análise da imagem do público-leitor no campo jornalístico - Umbelino Filho, José Eduardo Mendonça (2013)
This research intends to study how Goiânia´s press journalists define, understand and describe their audience. As a primary goal, the researchers seek to ascertain whether there is a shared image of the reader, which would be different from those images provided by the newspaper companies, the common-sense or other instances. Knowing that Media increases vagueness and doubt about to “whom we speak to”, we start from the premise that the journalists need to build up a picture of the audience. How they do it, based upon which cognitive subsidies, impressions or ideologies – that are relevant issues for this research.